Photobiomodulation (PBM): a therapeutic technique targeting fibroblast cell regeneration and survival in diabetic wounds - Jere, Sandy Winfield; Houreld, Nicolette Nadene (Frontiers in Photonics, 2024)
In injury, fibroblasts are key for disintegrating the fibrin clot, secreting collagen proteins, and constructing extracellular matrix (ECM). Altered fibroblast function is among the common characteristics of delayed wound healing and development of chronic wounds. Thus, treatment methods for effective wound healing require agents that affect the complexed wound milieu, including fibroblast cells. Diabetes mellitus (DM) is a common cause of impaired fibroblast cell function, delayed wound healing, development of chronic ulcers, and limb amputation. Photobiomodulation (PBM) promotes fibroblast cell proliferation, migration, release of growth factors and wound healing. Yet, its use is limited largely due to an incomplete understanding of its underlying mechanisms at the molecular and cellular level. In this review, we summarise the involvement of fibroblast cells in wound healing, and the effect of PBM on fibroblast cell function and diabetic wound healing. PubMed, Google Scholar, and Research Gate were used to find pertinent academic articles.